Conductive 3D microstructures by direct 3D printing of polymer/carbon nanotube nanocomposites via liquid deposition modeling. (September 2015) - Postiglione, Giovanni; Natale, Gabriele; Griffini, Gianmarco; Levi, Marinella; Turri, Stefano
Abstract: In this work, a new three-dimensional (3D) printing system based on liquid deposition modeling (LDM) is developed for the fabrication of conductive 3D nanocomposite-based microstructures with arbitrary shapes. This technology consists in the additive multilayer deposition of polymeric nanocomposite liquid dispersions based on poly(lactic acid) (PLA) and multi-walled carbon nanotubes (MWCNTs) by means of a home-modified low-cost commercial benchtop 3D printer. Electrical and rheological measurements on the nanocomposite at increasing MWCNT and PLA concentrations are used to find the optimal processing conditions and the printability windows for these systems. In addition, examples of conductive 3D microstructures directly formed upon 3D printing of such PLA/MWCNT-based nanocomposite dispersions are presented. The results of our study open the way to the direct deposition of intrinsically conductive polymer-based 3D microstructures by means of a low-cost LDM 3D printing technique.